Zinc-fingers and homeoboxes (ZHX) 2, a novel member of the ZHX family, functions as a transcriptional repressor. - Kawata, Hiroko (2003)
Zinc-fingers and homeoboxes (ZHX) 1 is a transcription factor that interacts with the activation domain of the A subunit of nuclear factor-Y (NF-YA). Using a yeast two-hybrid system, a novel ubiquitous transcription factor ZHX2 as a ZHX1-interacting protein was cloned. ZHX2 consists of 837 amino acid residues and contains two zinc-finger motifs and five homeodomains (HDs) as well as ZHX1. The mRNA is expressed among various tissues. ZHX2 not only forms a heterodimer with ZHX1, but also forms a homodimer. Moreover, ZHX2 interacts with the activation domain of NF-YA. Further analysis revealed that ZHX2 is a transcriptional repressor that is localized in the nuclei. Since ZHX2 shares a number of properties in common with ZHX1, we conclude that all these come under the ZHX family. The minimal functional domains of ZHX2 were then characterized. The dimerization domain with both ZHX1 and ZHX2 is the region containing HD1, the domain that interacts with NF-YA is the HD1 to HD2 region, the repressor domain is the HD1 to a proline-rich region. Lastly, using an immunoprecipitation assay, we showed that ZHX2 intrinsically interacts with NF-YA in HEK-293 cells and that ZHX2 represses the promoter activity of the cdc25C gene stimulated by NF-Y in Drosophila Schneider line 2 cells. Thus the ZHX family of proteins may participate in the expression of a number of NF-Y-regulated genes via a more organized transcription network.